2013
DOI: 10.1016/j.nicl.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Atypical excitation–inhibition balance in autism captured by the gamma response to contextual modulation

Abstract: Atypical visual perception in people with autism spectrum disorders (ASD) is hypothesized to stem from an imbalance in excitatory and inhibitory processes in the brain. We used neuronal oscillations in the gamma frequency range (30–90 Hz), which emerge from a balanced interaction of excitation and inhibition in the brain, to assess contextual modulation processes in early visual perception. Electroencephalography was recorded in 12 high-functioning adults with ASD and 12 age- and IQ-matched control participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 63 publications
3
71
0
Order By: Relevance
“…Additionally, it links well with the ASD symptom profile, as imbalance in localised excitatory-inhibitory processes can result in anomalous perception, such as the lack of context modulation characteristic of some forms of ASD symptom patterns (Coghlan et al, 2012;Rubenstein & Merzenich, 2003;Snijders, Milivojevic, & Kemner, 2013).…”
Section: Weak Central Coherence/enhanced Perceptual Processingmentioning
confidence: 90%
“…Additionally, it links well with the ASD symptom profile, as imbalance in localised excitatory-inhibitory processes can result in anomalous perception, such as the lack of context modulation characteristic of some forms of ASD symptom patterns (Coghlan et al, 2012;Rubenstein & Merzenich, 2003;Snijders, Milivojevic, & Kemner, 2013).…”
Section: Weak Central Coherence/enhanced Perceptual Processingmentioning
confidence: 90%
“…In addition, orientation discrimination thresholds are correlated with peak gamma frequency Dickinson, BruynsHaylett, Jones & Milne, 2015) providing further support for the link between neural inhibition, peak gamma frequency and orientation discrimination Although many studies 6 have measured gamma power in ASC (e.g. Snijders, Milivojevic & Kemner, 2013), to the best of our knowledge, peak gamma frequency in ASC has not yet been reported.…”
Section: Introductionmentioning
confidence: 91%
“…A number of authors have therefore suggested that gamma activity recorded through either EEG or MEG provides insight into the dynamics of E/I balance at a network level (e.g. Snijders et al, 2013). The vast majority of studies investigating gamma activity in ASD have measured gamma power, i.e.…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 99%